A comprehensive review of extrarenal manifestations of Autosomal Dominant Polycystic Kidney Disease (ADPKD) - Szczerek, Emilia; Płóciniczak, Viktoria (Quality in Sport, 2025)
Background: Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary kidney disease, primarily caused by mutations in the PKD1 and PKD2 genes. It is characterized by the progressive growth of numerous cysts in both kidneys, leading to renal failure. Beyond renal manifestations, ADPKD is associated with a wide spectrum of systemic complications, posing a significant clinical challenge and requiring comprehensive care. Aim: The aim of this paper was a comprehensive literature review regarding the extrarenal manifestations of autosomal dominant polycystic kidney disease (ADPKD), including their epidemiology, pathophysiology, and clinical significance. Materials and Methods: The review included scientific papers sourced from the PubMed and Google Scholar databases. Results: The most common extrarenal manifestation is autosomal dominant polycystic liver disease (ADPLD), with a prevalence reaching 94% in patients over 35; its development is strongly linked to extragenetic factors, mainly estrogen exposure. Cardiovascular manifestations are common and include hypertension (resulting, among other things, from RAAS activation), an increased frequency of aortic dilatation and aneurysms (44% of patients in one study), which raises the risk of dissection. Left ventricular hypertrophy (LVH) and valvular defects, especially mitral valve prolapse, are also frequent. Intracranial aneurysms (ICAs) occur in 9-12% of ADPKD patients (vs 3% in the general population), and their rupture tends to occur at a younger age. The most significant risk factor for ICAs is a positive family history. Conclusions: ADPKD is a multisystemic disease, not just a renal one. The wide range of extrarenal manifestations, including hepatic, cardiovascular, and cerebrovascular complications, highlights the necessity for comprehensive screening and the implementation of holistic patient care to identify, assess, and treat all health problems associated with this disease.